Presentation of the Dossier "History teaching: ethnicity and racial relations" - Bezerra, Antonio Alves; de Oliveira Lopes, Maria Aparecida (Revista Crítica Histórica, 2023)
Presentation of the Dossier "History teaching: ethnicity and racial relations".